Discourse Analysis Of Ecosystem Restoration, Green Economy, and Forest Conflict Issues In Jambi - Sarah Salamah; Ali Maksum (MASI Mandiri Edukasi, 2026)
Harapan Forest in Jambi Province represents one of Indonesia’s most prominent ecosystem restoration initiatives, yet its implementation has generated tensions between conservation objectives, green economy programs, and local livelihood interests. This study examines how ecosystem restoration, green economy initiatives, and forest conflicts are constructed and represented in public discourse surrounding the Harapan Forest. Using a qualitative approach, the research applies critical discourse analysis to 36 news articles published by Kompas.com and Tribun Jambi and analyzes the data using NVivo 12. The findings reveal three interconnected issues. First, a restoration dilemma emerges from competing priorities between biodiversity conservation and the economic dependence of local and indigenous communities on forest resources. Second, green economy initiatives, particularly social forestry and community partnership schemes, create opportunities for sustainable livelihoods but face challenges related to unequal access, land tenure disputes, and implementation constraints. Third, forest conflicts persist among local communities, indigenous groups, forest encroachers, PT Restorasi Ekosistem Indonesia (PT REKI), and state authorities over land management rights, resource access, and conservation regulations. The analysis further demonstrates the significant role of transnational actors, including BirdLife International, the Royal Society for the Protection of Birds, and international donors, in shaping restoration governance and conflict dynamics. This study contributes to the literature by providing a discourse-based analysis of ecosystem restoration that integrates environmental governance, green economy practices, and conflict dynamics, while highlighting the influence of transnational actors in Indonesia’s social forestry and restoration policies.